To the 60th birthday of Professor Vitaliy Sushchansky (Algebra and Discrete Mathematics, 2007)
This is a special issue of the journal devoted to the 60th birthday of an outstanding Ukrainian mathematician, one of the founders of our journal Professor Vitaliy Sushchansky.